Talent development environment in a professional football club in Norway. - Flatgård, G.; Larsen, C.; Sæther, S. A. (Scandinavian Journal of Sport and Exercise Psychology, 2020)
The research on talent development is increasing, even though most of it has focused on the individual athlete. By using a holistic and ecological approach to talent development and especially the players` environment, one could highlight how the environment facilitates player and team development. The purpose of this study was to analyse the recruit team of the professional football club Ranheim F.C. in Norway. Principal methods of data collection included interviews, participant observations of life in the environment, and analysis of documents. The environment was centred around the relationship between coaches and players, and although the supporting staff was relatively small, the inclusive and supportive approach from competent coaches was essential. The characteristics of the environment included that players were encouraged to take responsibility for their own development, exercise self-reflexiveness and the ability to handle the challenges that may arise in the life of young football players, and optimize the everyday lives of the players. Despite economic challenges within the club, the environment compensated with spirit, volunteerism, and hard work.